Changes in alanine aminotransferase levels after switching from tenofovir disoproxil fumarate (TDF) to tenofovir alafenamide (TAF) in HIV‐positive people without viral hepatitis in the Swiss HIV Cohort Study. Issue 7 (20th April 2021) - Kovari, H; Surial, B; Tarr, PE; Cavassini, M; Calmy, A; Schmid, P; Bernasconi, E; Rauch, A; Wandeler, G; Ledergerber, B; ,
Abstract : Objectives: We previously demonstrated an association between tenofovir disoproxil fumarate (TDF) and chronic liver enzyme elevation in the D:A:D study. The objective of the study was to assess changes in alanine aminotransferase (ALT) levels after switching from TDF to tenofovir alafenamide (TAF). Methods: We included Swiss HIV Cohort Study participants who switched from TDF to TAF with two or more ALT values in the 24 months before and two or more values in the 24 months after replacing TDF with TAF. Individuals with replicating viral hepatitis were excluded. Uni‐ and multivariable linear mixed models were used to explore changes in ALT values associated with switching from TDF to TAF, and to assess potential modifying effects. Results: A total of 1712 participants were included, contributing 6169 ALT values before and 5482 after switching. Median (interquartile range, IQR) age was 50 (42–57) years, and 75% were male. Median (IQR) ALT was 28 (22–38) U/L before and 24 (19–32) U/L after replacing TDF with TAF. ALT values decreased by 3.7 U/L (95% confidence interval: 3.2–4.2) after the switch. The median drop was larger in patients with chronic ALT elevation (defined as two or more elevated values for ≥ 6 months) compared with patients with normal ALT values (17.8 vs. 3.3 U/L, P < 0.001). We did not identify any major effect modifications of the ALT change with any of the potential variables studied. Conclusions: Replacing TDF with TAF in HIV‐monoinfected people led to a significant decrease in ALT values. Findings were not significantly affected by known risk factors for hepatotoxicity.